Sentimen Analisis Terhadap Investasi Halal: Studi Literatur Scopus - Mia Sari; Siti Sokhiful Jannah; Solahuddin Al- Ayubi (Mumtaz Publishing, 2024)
The purpose of this study was to investigate global sentiment towards halal investment, with a focus on the literature indexed in Scopus. Through sentiment analysis, this study aims to identify trends, positive and negative attitudes, as well as key factors that influence investors' perceptions of halal investment. As a Muslim-majority country, Indonesia should be the center of Islamic economic development in the world. The potential is also quite large, ranging from halal certification to concern for Muslim-friendly products, services that make it easier for Muslims to practice their faith, and much more. The strategy to achieve Indonesia's vision as the world's leading Islamic economic center is the strengthening of the halal value chain. This study examines halal investment as a component that is fundamental to the development of the halal industry in Indonesia. Based on the available literature, it was found that there is no sentiment research on this topic. The method used is descriptive statistical analysis with meta-analysis and sentiment analysis of secondary data in the form of metadata from 41 Scopus-indexed publications published in the last 25 years, starting in 1997 and ending in 2022. The results of sentiment analysis show that the response to halal investment developments tends to vary, with positive sentiment at 41.5%, negative sentiment at 17.1%, and neutral sentiment at 39.0%. The study also tries to identify negative responses to halal investments and offers ideas for future research.